Possible determination of temperature and space-time probable distribution of air temperature in the territory of the Republic of Armenia - Margaryan, Varduhi; Sedrakyan, Armen; Reshetchenko, Svitlana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Formulation of the problem. Climate studies cover a wide range of issues, from causes to consequences and adaptations to climate change, aimed at collectively addressing environmental protection, conservation, and sustainable use of natural resources within the framework of sustainable development goals (SDGs). Considering that air and soil, like any other terrestrial or astrophysical objects, are characterized by an important scalar physical quantity-temperature, which constantly changes in the Cartesian coordinate system, it is crucial to understand the features of its distribution. It has been established that temperature is considered a physical quantity that characterizes the degree of heat of an object. Given that modern physical studies describe temperature both from a thermodynamic perspective and statistically, according to the molecular-kinetic theory, which characterizes the average kinetic energy of the thermal motion of molecules and is measured on the Kelvin scale. In meteorology in many countries around the world, the temperature of air, soil, and water is typically measured in SI units, specifically in degrees Celsius (°C).The aim of the work. Analysis and assessment of regularities and features of the spatio-temporal distribution of air temperature for the period 1931-2021.Methods. The following methods were used in the work: mathematical-statistical, analysis, correlation methods, fundamental laws of modern physics were used in the work.Results. Actual data of temperature observations of meteorological stations of "Hydrometeorology and Monitoring Center" of RA Ministry of Environment, climate bulletins and chronicles were used as initial data sources. The temperature-heat (energy) difference becomes known in the sense that a system can have high energy but low temperature. Energy depends on the geometry (dimensions) of the system, but temperature does not. In the territory of the Republic of Armenia, a trend of increasing air temperature is observed, which is also a result of the entropy change of the system. It can be changed very quickly, depending on the process of disruption of excessive permissible norms of environmental factors in the given area, which currently needs separate serious research. The tendency to increase temperature indicators can be considered as the result of a change in the entropy of the system. This trend can change rapidly depending on the influence of excessive environmental factors in a certain area, which requires a separate and thorough study.